HUBUNGAN PENGGUNAAN JENIS MEDIA MASSA DENGAN PENGETAHUAN REMAJA TENTANG KESEHATAN REPRODUKSI DI SMAN 43 JAKARTA - Windi Kartika (2020)
Adolescence is a process of growth and development from childhood to adulthood. At this time adolescents have one characteristic which is high curiosity, that can trigger risky behavior if they get the wrong information. Providing appropriate information and comprehension can improve adolescent reproductive health knowledge. The purpose of this study was to determine the relationship of the use mass media types with adolescent's reproductive health knowledge at SMAN 43 Jakarta. The design of this study is descriptive analytic with cross sectional approach and sampling technique using purposive sampling based on predetermined criteria with a sample of 84 respondents with data collection using a questionnaire. Chi Square test results showed a significant relationship between the variables of mass media types use and adolescent reproductive health knowledge (p-value = 0.043). Good reproductive health information can influence reproductive health knowledge in adolescents and create good attitudes and behaviors.